2009
DOI: 10.2989/salals.2009.27.3.11.945
|View full text |Cite
|
Sign up to set email alerts
|

Writer identity while learning discipline-specific academic literacy in an additional language

Abstract: Constructing an effective identity in academic writing is considered crucial in establishing a favourable reader-writer relationship; in eliciting a positive reader response to the text and even in developing a convincing argument (Hyland, 2004). But different expectations of authorial presence in academic writing between disciplines, and even changing notions within disciplines, present student learners of academic literacy with difficulties. These difficulties are increased for students writing in English as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There is by now a considerable body of literature which analyses the linguistic challenges and writing development processes of first-year university students from second-language/ marginalised/ disadvantaged educational backgrounds (see for example Clark & Ivanič, 1997;Herrington & Curtis, 2000; Thesen & Van Pletzen, 2006;Granville & Dison, 2009;Stacey, 2009). These studies have shown that becoming proficient in academic literacy is intimately connected to identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is by now a considerable body of literature which analyses the linguistic challenges and writing development processes of first-year university students from second-language/ marginalised/ disadvantaged educational backgrounds (see for example Clark & Ivanič, 1997;Herrington & Curtis, 2000; Thesen & Van Pletzen, 2006;Granville & Dison, 2009;Stacey, 2009). These studies have shown that becoming proficient in academic literacy is intimately connected to identity.…”
Section: Introductionmentioning
confidence: 99%
“…The participants in our study are all from disadvantaged educational backgrounds and/ or are speakers of English as a second language.2 They were (with the exception of one student) the first in their families, sometimes the first in their communities, to attend university. The project tracked their shifts in language and literacy attitudes and practices and in constructions of self over the course of their undergraduate years.There is by now a considerable body of literature which analyses the linguistic challenges and writing development processes of first-year university students from second-language/ marginalised/ disadvantaged educational backgrounds (see for example Clark & Ivanič, 1997;Herrington & Curtis, 2000; Thesen & Van Pletzen, 2006;Granville & Dison, 2009;Stacey, 2009). These studies have shown that becoming proficient in academic literacy is intimately connected to identity.…”
mentioning
confidence: 99%
“…Often, absences or silences reveal a lot about bias. For instance, research on academic literacy, the knowledge of discipline-specific language and genres, focuses on participants for whom, just like for the second author of this chapter, English is an additional language [16][17][18] and ignores the needs of domestic or native-speaking students. The gap may indicate that students are expected to require more training in academic literacy even though, as mentioned above, academic literacy has more to do with discipline-specific skills than language proficiency.…”
Section: Literature Review 21 Students In the Context Of Higher Educa...mentioning
confidence: 99%
“…The notion of multiple writer identities, particularly for ESL learners has also been reported to influence students' engagement with academic writing (Li, 2007;Stacey, 2010). In fact, in order to perform successfully in the academic community, learners need to adopt the appropriate writer identity (Ivanic, 2006;Wenger, 1998) in order to gain acceptance as a full member of the community of practice (Huhtala & Lehti-Eklund, 2010, p. 273).…”
Section: Engagement With Academic Writingmentioning
confidence: 99%